2013
DOI: 10.1017/s0950268813001039
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the burden of pertussis in young children on hospitals and emergency departments: a study using linked routinely collected data

Abstract: Potential underestimation of the health system burden of pertussis was investigated by linking administrative datasets including pertussis notifications, hospitalizations and emergency department (ED) presentations for 1 304 876 children aged <15 years in NSW, Australia. From 2005 to 2008, 3006 children had a pertussis notification, 455 were hospitalized and 644 had an ED presentation with a coded diagnosis of pertussis. Linking hospital and ED records with pertussis notifications identified 140 hospitalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The true hospitalisation rates in Sweden may be underestimated, as the trigger point for investigation was a positive laboratory sample. Others have demonstrated that linking of datasets may detect additional infants with hospital admissions, including presentation to emergency rooms [13]. This capturerecapture analysis is yet to be done in Sweden.…”
Section: Discussionmentioning
confidence: 99%
“…The true hospitalisation rates in Sweden may be underestimated, as the trigger point for investigation was a positive laboratory sample. Others have demonstrated that linking of datasets may detect additional infants with hospital admissions, including presentation to emergency rooms [13]. This capturerecapture analysis is yet to be done in Sweden.…”
Section: Discussionmentioning
confidence: 99%
“…26 Although pertussis infection among immunized children 2 to 3 years uncommonly results in hospitalization, those not hospitalized may have symptoms severe enough to lead to emergency department presentation, and both hospital and emergency department presentation are underestimated. 27 Importantly, children 2 to 3 years of age commonly have younger siblings and may play an important role in the transmission of infection to unimmunized infants, vulnerable to severe disease. [28][29][30] Of the few studies of field effectiveness of acellular pertussis vaccines in children ,5 years of age, [3][4][5][6] none separately estimated VE for the first and second year of life or evaluated changes in VE after 2 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…There are 186 designated EDs, ranging from small rural multipurpose centres to large metropolitan tertiary teaching hospital EDs. The Emergency Department Data Collection (EDDC) system is a population‐level registry that collated information from all EDs across NSW . The Demand for Emergency Service Trends in Years 2010–2014 (DESTINY 10–14) project was undertaken to understand the drivers of current ED presentation trends in NSW.…”
Section: Introductionmentioning
confidence: 99%